Pembangunan Sosial Ekonomi di Indragiri Hilir Riau Perspektif Teori Kebijakan Fiskal Abdul Mannan - Salmia Salmia (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Fiscal Policy is a government’s policy related to regional and national income and expenditure. This policy is very important in a region because this policy not only discusses how a region or state gets fund and utilizes the fund to develop the region, but also discusses how fiscal policy is able to create development and prosperity for people’s socio-economic life. The glory of Islam in the past has also convinced people that the economic development system that was used could survive and had a well-known history, so the theory of Abdul Mannan, who was a contemporary Muslim economist, could be used, expecting that the glory of Islamic countries in the past could be repeated nowadays. Mannan wrote in his fiscal policy perspective based on Islamic law. The core of Mannan’s fiscal policy in socio-economic development is the principles of happiness (at-targib) for society and socio-economic improvement, as well as spiritual and moral development. Therefore, this study focused on the Situation of Socio-Economic Development of Indragiri Hilir Regency whose majority of the population is Moslem; whether the implementation of fiscal policy in Indragiri Hilir has been relevant to Mannan’s theory. Such question could be answered after conducting a research in Indragiri Hilir using interview technique to several informants from Local Government Officials, Members of Parliament and Indragiri Hilir Society. The results showed that the development in Indragiri Hilir focuses more on plantation development because the majority of population works as farmers and gardening. In addition, several things that are not yet relevant are: non conducive regional bureaucracy and uneven infrastructure development.